2010
DOI: 10.21236/ada538015
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Managing the Career Continuance of Enlisted Soldiers

Abstract: The U.S. Army Research Institute for the Behavioral and Social Sciences (ARI) implemented a large research program titled "STAY: Strategies to Enhance Retention." The enlisted portion of the STAY project identified factors influencing enlisted Soldiers' career continuance decisions, developed a model of the decision process, generated an extensive list of attrition and retention interventions, and evaluated two of them. Interviews and focus groups across Training and Doctrine Command (TRADOC) and Forces Comman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Reducing cadets' turnover is crucial for military organization, because of the direct and high costs associated with cadets' turnover (i.e., the military wastes about $35,000-$60,000 for each cadet who abandons his/her military organization; see Strickland, 2005), as well as for the indirect costs associated with low motivation (see Dupré & Day, 2007;Young et al, 2010).…”
Section: From Organizational Socialization To Turnover Intentions Through Organizational Identificationmentioning
confidence: 99%
“…Reducing cadets' turnover is crucial for military organization, because of the direct and high costs associated with cadets' turnover (i.e., the military wastes about $35,000-$60,000 for each cadet who abandons his/her military organization; see Strickland, 2005), as well as for the indirect costs associated with low motivation (see Dupré & Day, 2007;Young et al, 2010).…”
Section: From Organizational Socialization To Turnover Intentions Through Organizational Identificationmentioning
confidence: 99%
“…Career development and career planning are primarily formalities in the military. For a country like the United States, Young et al (2010) reported that attrition and retention among the U.S. Army Soldiers are taken seriously to help sustain a strong volunteer force.…”
Section: Introductionmentioning
confidence: 99%